Denitrifying bacteria in the limnetic zone of Lake Tota, Colombia - Julián Esteban Másmela-Mendoza, Luz Marina Lizarazo-Forero (Universitas Scientiarum)
The objective of study was to isolate and determine the identity of denitrifying bacteria from limnetic areas of Lake Tota (Colombian Andes) with and without rainbow trout production activities. We examined the relationships between the lake’s physicochemical factors (oxygen, nitrogen, and phosphorus content) and two bacterial communities (denitrifying bacteria and coliforms). Water samples were taken 20 m below the surface from July to September at five limnetic zones; two of which were close to rainbow trout farming areas. In each zone, the concentrations of oxygen, nitrogen, and phosphorus were measured. To identify and quantify the abundance of bacteria, the most probable number (MPN) technique was used, employing minimal medium for denitrifying bacteria and medium for nitrate reducing bacteria (NRB). A greater number of denitrifying bacteria were found in the fish farming zones, identifying bacteria of the genera Bacillus, Pseudomonas, Nocardia, and Streptomyces. The number of nitrate-reducing bacteria revealed statistically significant differences throughout the sampling period, increasing from July to September and was related to a decrease in precipitation. The density of NRB and total phosphorus were directly correlated. High bacterial densities of denitrifying bacteria and coliforms are indicative of changes from oligotrophic to eutrophic states in the studied limnetic areas.